Educational Leaders Without Borders: Rising to Global Challenges to Educate All - Papa, Rosemary (Springer, 2015)
Building from the history of inequality in education up to current problems, this text posits viewpoints on how to cultivate humanistic leaders in education to best benefit underserved children around the world. Among perspectives examined are economic, cultural, and political circumstances that benefit some and harm others, creating educational inequality. To illustrate the work that must be done, this book connects vignettes of compelling school issues to educational philosophies, e.g., Makiguchi’s work, to bridge the theoretical and the practical and pose real solutions.